Copper in Mangrove Environment: Current Status in Soil, Water and Plant at Sepang-Lukut Mangrove Forest, Malaysia - Hossain, Mahmood (1998)
This study presents copper concentrations and distributions in Sepang-Lukut mangrove forest, Malaysia. This mangrove ecosystem is mainly polluted from different sources like waste from pig farms, oil palm industries and house hold waste. Untreated waste discharge from pig farms may be responsible for copper pollution in this forest area as copper sulphate has been used in the farms in the diet of pigs for protection from pathogenic disease. Untreated wastes are discharged directly into the Sepang Sesar river which is situated in the Sepang-Lukut mangrove forest ecosystem. Six stations were chosen for the study starting from the discharge point at every 2 km interval towards sea. Total and available copper in soil and copper content in infiltration water were measured for each station. Copper content was also measured in river water adjacent to each station. Copper absorption and it's distribution in leaf, stem and root of Rhizophora mucronata seedlings were measured at the last three stations towards the sea. Soil is the main reservoir of total and available copper content in the mangrove forest. Highest total and available copper concentration in soil was found in the stations nearest to the discharge point and decreased towards the stations near to the sea. The means of total and available soil copper content were 145 µg/g (ranged from 1.20 to 703.90 µg/g) and 36 µg/g (ranged from 0.74 to 103.21 µg/g) respectively. Available soil copper found to positively correlate with total soil copper, soil organic matter content and CEC. Total soil copper also found to positively correlate with soil organic matter content, soil CEC, total dissolved solids and in situ pH. On the other hand, the mean concentration of copper in river and infiltration water were 0.07 mg/l and 0.04 mg/l respectively. Infiltration water copper content found to positively correlate with river water copper content. River water copper concentration found to positively correlate with redox potential and negatively correlate with dissolved oxygen and salinity. Highest copper concentration in Rhizophora mucronata seedling parts were detected at Station 4 and roots attained the highest (9.24 µg/g) followed by stem (3.12 µg/g and leaves (3.10 µg/g). Copper concentration in seedling parts at Station 5 showed same trend like Station 4, where roots contained highest (2.84 µg/g) followed by leaves (2.39 µg/g) and stem (1.82 µg/g). But leaves contained the highest (2.25 µg/g) followed by stem (1.64 µg/g) and roots (1.54 µg/g) at Station 6.